Konsep Kepemimpinan Islam: Studi Komparatif Al-Qur’an dan Hadis - Fika Ratna Pratiwi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the Islamic perspective, leadership is a mandate and responsibility that must be held accountable in front of those who are led and Allah SWT. Leadership responsibilities in Islam are not only horizontal between fellow humans, but also vertical to Allah SWT. The purpose of this research is to provide a comprehensive understanding of the concept of leadership in Islam by analyzing various verses of the Qur'an and relevant hadith. This research is included in the category of library research, because it analyzes documents and sources of information related to what is being researched. While the method used is a comparative method, which is a method that compares various data, theories, or concepts from different sources to find relevant equations, differences, or patterns. From the results of this study, it can be explained that the concept of leadership in Islam based on the Qur'an includes three main principles: humans as caliphs, the principle of faith, and ulil amri. Meanwhile, the concept of leadership in the Prophet's hadith describes various characteristics that a leader must have, including leadership spirit, professionalism, ability to carry out duties, conformity with the aspirations of the people, and involvement in deliberation.